2018
DOI: 10.1073/pnas.1717077115
|View full text |Cite
|
Sign up to set email alerts
|

Entropy drives selective fluorine recognition in the fluoroacetyl–CoA thioesterase from Streptomyces cattleya

Abstract: Fluorinated small molecules play an important role in the design of bioactive compounds for a broad range of applications. As such, there is strong interest in developing a deeper understanding of how fluorine affects the interaction of these ligands with their targets. Given the small number of fluorinated metabolites identified to date, insights into fluorine recognition have been provided almost entirely by synthetic systems. The fluoroacetyl-CoA thioesterase (FlK) from thus provides a unique opportunity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…S1 †). The reaction was monitored by 19 F-NMR analysis. However, there was no apparent new organofluorine signal appearing in the 19 F-NMR spectrum while 4-FT 2 from the FTaseMA biochemical reaction accumulated, suggesting that the fluorine atom at the C4 position of 4-FT 2 strongly inhibits the reactivity of LAAO.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 †). The reaction was monitored by 19 F-NMR analysis. However, there was no apparent new organofluorine signal appearing in the 19 F-NMR spectrum while 4-FT 2 from the FTaseMA biochemical reaction accumulated, suggesting that the fluorine atom at the C4 position of 4-FT 2 strongly inhibits the reactivity of LAAO.…”
Section: Resultsmentioning
confidence: 99%
“…1B). [17][18][19] The detoxification mechanism of 4-FT 2 employed by S. cattleya has also been extensively elaborated by the study of FthB and FthC, the fluorothreonyl-tRNA deacylase and 4-FT transporter, respectively. The structural similarity between 4-FT 2 and L-Thr allows 2 to form a misacylated tRNA, 4-FT-tRNA, hence entering the ribosomal protein biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the mechanism of selective fluorination, a comprehensive strategy was implemented for FLK including thermodynamic, kinetic, and biophysical experiments. These studies indicated that entropy drive mediated by hydrophobicity and solvation is the key to selective fluorination recognition, especially the substrate-binding controlled by the active site Phe36 (Figure S4 ) (Weeks et al 2018 ). Moreover, the selectivity to the fluoroacetyl-CoA substrate not only depends on the polarization provided by the negatively charged fluorine substitution but also on the molecular recognition of fluorine during the formation of acyl-FLK intermediate (Weeks et al 2014 ).…”
Section: Enzymatic Synthesis Of Fluorinated Compoundsmentioning
confidence: 99%
“…The fluoroacetyl-CoA hydrolase (FlK) and a trans acting fluorothreonyl-tRNA deacylase (FthB) is part of this enzymatic machinery in S. cattleya. [209,210,211] FlK enzyme hydrolyze fluoroacetyl-CoA, whereas FthB removes the misacylation and incorporation of fluorothreonyl-tRNA instead of L-threonine into proteins during the synthesis.…”
Section: Engineering Natural Product Pathways With Sam-dependent Halomentioning
confidence: 99%